2020
DOI: 10.1155/2020/1206402
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Thrombus Formation Despite Continuous Non-Vitamin K Antagonist Oral Anticoagulant Therapy in Atrial Fibrillation Patients Undergoing Electrical Cardioversion or Catheter Ablation: A Comparison of Dabigatran and Rivaroxaban

Abstract: Left atrial appendage thrombus (LAAT) may be detected by transesophageal echocardiography (TOE) in patients with atrial fibrillation (AF) despite continuous anticoagulation therapy. We examined the factors predisposing to LAAT in patients treated with the anticoagulants dabigatran and rivaroxaban. We retrospectively evaluated 1,256 AF patients from three centres who underwent TOE before electrical cardioversion (n = 611, 51.4%) or catheter ablation (n = 645, 48.6%) from January 2013 to December 2019 and had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In comparison to the aforementioned studies, in our study, the incidence of LAA thrombus was slightly higher. It is worth noting that our study group had a higher incidence of comorbidities and known predictors of embolic complications, such as mean age (73.4 years), a higher mean CHA 2 DS 2 VASc score (3.83), and higher incidence of hypertension (89.4%), heart failure (33.1%), diabetes mellitus (37.5%), and vascular disease (26.9%), in comparison to previously published studies [ 12 14 , 16 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In comparison to the aforementioned studies, in our study, the incidence of LAA thrombus was slightly higher. It is worth noting that our study group had a higher incidence of comorbidities and known predictors of embolic complications, such as mean age (73.4 years), a higher mean CHA 2 DS 2 VASc score (3.83), and higher incidence of hypertension (89.4%), heart failure (33.1%), diabetes mellitus (37.5%), and vascular disease (26.9%), in comparison to previously published studies [ 12 14 , 16 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 56%
“…In a study by Frenkiel et al [ 16 ], thrombus was found in 5.4% of patients treated with dabigatran, 4.8% treated with rivaroxaban, and 0% treated with apixaban. Also, Gorczyca et al [ 18 ], showed that the incidence of LAA thrombus was comparable between dabigatran and rivaroxaban, at 5% and 3.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Gorczyca et al retrospectively evaluated 1,256 AF patients on dabigatran or rivaroxaban and revealed a 4.1% TEE thrombus detection rate prior to DCC or catheter ablation, regardless of the anticoagulant agent used. However, the significant LAAT predictors in patients treated with dabigatran were non-paroxysmal AF (vs. paroxysmal AF), heart failure, and an eGFR <60 ml/min/1.73 m 2 ; the predictors in patients treated with rivaroxaban were non-paroxysmal AF (vs. paroxysmal AF) and heart failure [33]. Jaroch et al retrospectively evaluated 202 patients with persistent AF who underwent TEE before electrical cardioversion and revealed presence of LAAT/sludge in 31 and a spontaneous echo contrast in 25 subjects.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, in the presented study, AF type or impaired kidney function were not shown to be the predictors of OAC use in patients at low thromboembolic risk. It has been reported that the aforementioned factors increase the risk of thromboembolic complications in patients with AF or predispose them to thrombus formation in the left atrial appendage [8][9][10][11][12][13][14][15][16][17][18][19][20]. Study results connected with anticoagulant overtreatment of patients with AF prove that it is common and most likely stems from using OACs due to temporary indications to anticoagulant therapy and from the presence of thromboembolic risk factors not included in the CHA 2 DS 2 -VASc score.…”
Section: Discussionmentioning
confidence: 99%